2023
DOI: 10.3390/ijms24076551
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Therapeutic Potential of Irisin: Harnessing Its Function in Degenerative Disorders and Tissue Regeneration

Abstract: Physical activity is well-established as an important protective factor against degenerative conditions and a promoter of tissue growth and renewal. The discovery of Fibronectin domain-containing protein 5 (FNDC5) as the precursor of Irisin in 2012 sparked significant interest in its potential as a diagnostic biomarker and a therapeutic agent for various diseases. Clinical studies have examined the correlation between plasma Irisin levels and pathological conditions using a range of assays, but the lack of rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…It is widely accepted that physical exercise has antidegenerative and renewal properties, and myokines are the leading mediators of these beneficial effects. Irisin is primarily involved in maintaining muscle cell and bone health thanks to its anti-inflammatory [ 228 ] and regenerative properties [ 229 ]. Mechanistic studies have shown a close association between irisin deficiency and the development of insulin resistance and cardiometabolic complications, such as pathological myocardial remodeling [ 230 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…It is widely accepted that physical exercise has antidegenerative and renewal properties, and myokines are the leading mediators of these beneficial effects. Irisin is primarily involved in maintaining muscle cell and bone health thanks to its anti-inflammatory [ 228 ] and regenerative properties [ 229 ]. Mechanistic studies have shown a close association between irisin deficiency and the development of insulin resistance and cardiometabolic complications, such as pathological myocardial remodeling [ 230 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Osteocalcin, a protein involved in building bones and controlling glucose levels, is also affected. The mechanical stress on bones during resistance training is thought to increase the production of osteocalcin, which improves bone density and controls glucose levels [ 11 ].…”
Section: Introductionmentioning
confidence: 99%